2020
DOI: 10.1371/journal.pone.0227512
|View full text |Cite|
|
Sign up to set email alerts
|

The role of peer, parental, and school norms in predicting adolescents’ attitudes and behaviours of majority and different minority ethnic groups in Croatia

Abstract: Social norms in general have an important role in the regulation of intergroup relations. However, the effects of one specific type of social norms-in-group norms about intergroup contact-have not yet been extensively studied, especially among groups of different status or in different intergroup contexts. The purpose of this research was to examine the effects of three types of contact norms (peer, parental and school) on four intergroup outcomes (ingroup bias, social distance, tendency to discriminate, proso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…For example, increased intergroup contact in integrated education that promoted empathy and self-disclosure has been linked with more positive intergroup relations in NI (Turner et al, 2013). Similar shared education initiatives have been investigated in the RNM (Loader et al, 2018) and Kosovo and have been found to shape intergroup norms (Pehar et al, 2020) while providing greater opportunities for outgroup prosocial behavior. Where shared education practices are not possible, interventions that use media or vicarious contact may also help to increase prosocial justifications to resolve tension in a conflict-affected society (Cole et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…For example, increased intergroup contact in integrated education that promoted empathy and self-disclosure has been linked with more positive intergroup relations in NI (Turner et al, 2013). Similar shared education initiatives have been investigated in the RNM (Loader et al, 2018) and Kosovo and have been found to shape intergroup norms (Pehar et al, 2020) while providing greater opportunities for outgroup prosocial behavior. Where shared education practices are not possible, interventions that use media or vicarious contact may also help to increase prosocial justifications to resolve tension in a conflict-affected society (Cole et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies, for example, have suggested that adolescence is a particularly critical period for identity and values to develop (Vollebergh et al, 2001), but noted that as children grow more autonomous and experience other influences such as peers or the media, parental influence may decrease (Schönpflug, 2001). This is particularly relevant in postconflict settings where civic and peer norms shape the characterization of groups and how they are perceived and treated (Pehar et al, 2020; Tankard & Paluck, 2016).…”
Section: Transgenerational Impact Of the 1994 Genocidementioning
confidence: 99%
“…For instance, a longitudinal study of ethnic majority German adolescents (12-16 years old) found that the strongest correlation between parents' and adolescents' attitudes was between the ages of 12 and 13 and weakened as adolescents got older (Gniewosz & Noack, 2015). A cross-sectional study of ethnic majority and minority adolescents in Croatia found that the relation between parental norms and adolescents' outgroup attitudes was stable between the ages of 11 to 18 (Pehar et al, 2020). Although there are too few studies to draw conclusive developmental implications, they highlight how congruence between parent and children's intergroup attitudes could fluctuate depending on the developmental period.…”
Section: Families In Marginalized Positions As a Source Of Support In...mentioning
confidence: 99%